2020
DOI: 10.1155/2020/6406439
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Treatment Considerations Differ across Surgical Subspecialties Treating Malignant Peripheral Nerve Sheath Tumors: An International Survey

Abstract: Background. Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive soft tissue sarcomas (STS) that, because of their origin, are operated by several surgical subspecialties. This may cause differences in oncologic treatment recommendations based on presentation. This study investigated these differences both within and between subspecialties. Methods. A survey was distributed among several (inter)national surgical societies. Differences within and between subspecialties were analyzed by χ2-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…3 , 5 , 24 Nonetheless, a recent survey showed that many surgeons operating on MPNSTs are hesitant to perform less extensive resections regardless of surgical subspecialty. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , 5 , 24 Nonetheless, a recent survey showed that many surgeons operating on MPNSTs are hesitant to perform less extensive resections regardless of surgical subspecialty. 25…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons emphasize the need for fresh-frozen coupes preoperatively or even resecting more of the originating nerve as skip lesions may be present. 2,25,37,38 Whenever adequate margins have been obtained, early reconstructions show superior results over delayed reconstructions. [39][40][41] Early reconstructions are generally less complex as tissue fibrosis is less extensive, which ameliorates nerve and vessel identification, in turn decreasing possible complications.…”
Section: Combining Oncological Treatment and Reconstructionsmentioning
confidence: 99%
“…Some argue that this may be due to its perineural origin, and microscopic skip lesions may be present along the nerve [70]. In a recent survey, several surgeons would advocate possibly resecting more of the nerve of origin, but this has not been studied in a clinical setting [71]. Fresh frozen coupes may be indicated intraoperatively to ascertain complete resection in nerve endings [10,12,70].…”
Section: Surgical Marginsmentioning
confidence: 99%